Quest of the overself : the classic work on how to achieve serenity of mind - "Bruton, Paul" (London, 2003)
The Quest of the Overself shows Western readers how to achieve serenity of mind, control of thought and desire, and the power to use higher forces by means of simple exercises. These include breathing and visualisation as well as mental control through meditation. These ideas, which the author gained by extensive travel in India, are as relevant to us today as they were when first published in 1937. Paul Brunton was a British philosopher, mystic and traveler. He left a successful journalistic career to live among yogis and holy men and studied a wide variety of Eastern and Western esoteric spiritual traditions. As he explains in the still fresh and fascinating The Quest of the Overself, meditation and the quest for inner peace are by no means exclusively for monks and hermits but also support those living everyday, active lives in the West.
Keywords: "Mind, serenity of"